Functional SARS-CoV-2 cross-reactive CD4 + T cells established in early childhood decline with age - Marion Humbert; Anna Olofsson; David Wullimann; Julia Niessl; Emma B. Hodcroft; Curtis Cai; Yu Gao; Ebba Sohlberg; Robert Dyrdak; Flora Mikaeloff; Ujjwal Neogi; Jan Albert; et al. (2023)
Pre-existing SARS-CoV-2-reactive T cells have been identified in SARS-CoV-2-unexposed individuals, potentially modulating COVID-19 and vaccination outcomes. Here, we provide evidence that functional cross-reactive memory CD4 + T cell immunity against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is established in early childhood, mirroring early seroconversion with seasonal human coronavirus OC43. Humoral and cellular immune responses against OC43 and SARS-CoV-2 were assessed in SARS-CoV-2-unexposed children (paired samples at age two and six) and adults (age 26 to 83). Pre-existing SARS-CoV-2-reactive CD4 + T cell responses targeting spike, nucleocapsid, and membrane were closely linked to the frequency of OC43-specific memory CD4 + T cells in childhood. The functional quality of the cross-reactive memory CD4 + T cell responses targeting SARS-CoV-2 spike, but not nucleocapsid, paralleled OC43-specific T cell responses. OC43-specific antibodies were prevalent already at age two. However, they did not increase further with age, contrasting with the antibody magnitudes against HKU1 (β-coronavirus), 229E and NL63 (α-coronaviruses), rhinovirus, Epstein–Barr virus (EBV), and influenza virus, which increased after age two. The quality of the memory CD4 + T cell responses peaked at age six and subsequently declined with age, with diminished expression of interferon (IFN)-γ, interleukin (IL)-2, tumor necrosis factor (TNF), and CD38 in late adulthood. Age-dependent qualitative differences in the pre-existing SARS-CoV-2-reactive T cell responses may reflect the ability of the host to control coronavirus infections and respond to vaccination.